Effect of Jump Direction on Joint Kinetics of Take-Off Legs in Double-Leg Rebound Jumps - Yasushi Kariyama (MDPI AG, 2019)
Vertical (VDJ) and horizontal (HDJ) double-leg rebound jumps are used as plyometric exercises in direction-specific training regimens for various sports. We investigated the effects of jump direction on joint kinetics of the take-off legs in double-leg rebound jumps. Twelve Japanese male track and field athletes performed VDJ, 100% HDJ, 50% HDJ (50% of 100% HDJ distance), and 75% HDJ (75% of 100% HDJ distance). Kinematic and kinetic data in the sagittal plane were calculated using a force platform and high-speed video camera. Hip negative power during the eccentric phase decreased from VDJ to 50% HDJ (VDJ, −4.40 ± 4.25 W/kg; 50% HDJ, −0.83 ± 2.10; 75% HDJ, −0.33 ± 0.83; 100% HDJ, 0 ± 0), while hip positive power increased from VDJ to 100% HDJ (VDJ, 4.19 ± 2.73 W/kg; 50% HDJ, 9.37 ± 2.89; 75% HDJ, 11.15 ± 3.91; 100% HDJ, 18.51 ± 9.83). Knee negative power increased from VDJ to 75% HDJ (VDJ, −14.48 ± 7.67 W/kg; 50% HDJ, −18.98 ± 7.13; 75% HDJ, −21.57 ± 8.54; 100% HDJ, −23.34 ± 12.13), while knee positive power decreased from VDJ to 75% HDJ (VDJ, 23.18 ± 9.01 W/kg; 50% HDJ, 18.83 ± 5.49; 75% HDJ, 18.10 ± 5.77; 100% HDJ, 16.27 ± 6.22). Ankle joint kinetics remained unchanged. Differences in hip and knee joint kinetics between VDJ and HDJ were associated with direction control, becoming more pronounced as jump distance increased.